From high-risk sports to sports as high risk: Crisis, capitulation and creativity during COVID-19 (Alternation African Scholarship Book Series, 5, 2020)
The COVID-19 pandemic has impacted sport, spanning grassroots level up to and including elite sport, and has led to differential outcomes for people from a variety of socio-economic backgrounds. While COVID-19 casts a shadow over sport and probably will continue for years to come, this book offers some perspectives and reflections that will inform academic discourses and help to influence sport policy as well as practice. The book highlights the influences of the pandemic on sports participation and the sports industry predominantly in South Africa. Sport in schools and communities in Zimbabwe are also dealt with, specifically sport as part of the school curriculum and the impact of the pandemic on the livelihood of people who depend on sport events and activities as source of income or revenue. With contributions from seasoned and novice academics, athletes and researchers, this book offers insight on various levels. The approaches include auto-ethnographic and case studies, using various scales of analysis across a range of topics and practical areas, including neoliberalism in sport and the impacts of COVID-19 on sporting activities and society. The book will be of interest to academics, researchers, students, practitioners, the media, policy-makers, to name a few. It is a timely addition to the growing body of knowledge regarding the pandemic, and its impact on sport. I would like to thank the authors, reviewers, Editorial Advisory Committee members, editorial team and administrative personnel who have worked together to ensure the timeous production of this book.